Permutation Induced Shuffling Based Block Cipher For Real-Time Applications - Radha, N.; Venkatesulu, M. (Malaysian Journal of Computer Science, 2014)
We proposed a novel non-conventional full encryption approach designed to accommodate fast performance and security with low computational complexity for real-time video communications. The proposed cipher employs the confusion and diffusion component simultaneously through the shuffler operator S and confusion component through the randomized substitution R in a binary tree. A pseudo random integer sequence π generates the round keys and also used to define the non-linear confusion and diffusion components. The advantages of these components are 1) they do not require storage space, when compared to generation and storage of S-boxes in other systems. 2) they are faster. We analyzed our approach in terms of efficiency and security from a cryptographic view point. We analyzed performance by comparing with the symmetric algorithms AES and RC6. Experimental results showed that the proposed algorithm works faster in terms of encryption time and frame rate and thus suitable for rendering the data in real-time by the receiver’s playback. Histogram analysis, correlation analysis and differential cryptanalysis proved the efficiency of the cipher.